Makna Simbolik Tari Turyantapadha di Kecamatan Turen, Kabupaten Malang, Jawa Timur - Nurma, Alfiyah; Iswatiningsih, Daroe (University of Brawijaya, 2025)
One of the arts found in Turen District, Malang Regency is the Turyantapadha Dance. This study aims to (1) describe the form of presentation and meaning of the Turyantapadha Dance movements, and (2) describe the symbolic meaning of the costumes and musical accompaniment used in the Turyantapadha Dance. This type of research is descriptive qualitative with a semiotic approach in describing local regional arts. The source of research data and research data is the Turyantapadha Dance art in Turen District, Malang Regency. The data collection technique for this study is interviews and literature studies. The results of this study, namely, first, overall the Turyantapadha Dance movement consists of four movements, namely panembahan as well as an opening section, bumi langit, tumpang tali, and kesatrean. Second, the clothes or costumes used in the Turyantapadha Dance are dominated by three colors, namely blue, red and gold. Each color has a meaning related to the history of Turen District. Third, the musical accompaniment used in the Turyantapadha Dance uses gamelan music as one of the typical Javanese music combined with tambourines as a representation of the Islamic religion which is widely practiced by the community in general.